2022
DOI: 10.7759/cureus.25050
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Surgical Strategies for Pilonidal Sinus Disease in the Netherlands

Abstract: Purpose Pilonidal sinus disease (PSD) is a subcutaneous infection of the sacrococcygeal region due to entrapment of hair and/or debris. International guidelines recommend minimally invasive techniques and flap techniques. A Dutch guideline for the treatment of PSD is not available and this may lead to practice variation. The aim of this study was to perform a national survey on the surgical treatment of PSD in the Netherlands. Method An online survey was sent by e-mail to all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…A majority of the participating surgeons in our study reported to use flap procedures. This is in contrast to findings from a recent study that reported an infrequent use of flap techniques (22.6%) by Dutch surgeons [28]. It seems like most hospitals in Norway have followed the example of The University Hospital of North Norway, Tromsø, that introduced this technique as their standard procedure for all symptomatic, chronic PSD already in 2002 [29].…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…A majority of the participating surgeons in our study reported to use flap procedures. This is in contrast to findings from a recent study that reported an infrequent use of flap techniques (22.6%) by Dutch surgeons [28]. It seems like most hospitals in Norway have followed the example of The University Hospital of North Norway, Tromsø, that introduced this technique as their standard procedure for all symptomatic, chronic PSD already in 2002 [29].…”
Section: Discussioncontrasting
confidence: 76%
“…Currently, the specialization in general or gastrointestinal surgery in Norway does not require a specific number of PSD procedures performed. Like numbers from other countries, a large proportion of the surgeons performing PSD surgery in current practice performed fewer than ten PSD operations per year [11,27,28]. This indicates that it may take longer time to achieve competence in PSD surgery.…”
Section: Discussionmentioning
confidence: 99%
“…He personally advocated closed excision but admitted that the reported incidence of failure for that procedure ranged from less than 1% to 50%. Currently, there is a dichotomy among the world's surgeons regarding the treatment of this disease and many have not yet deviated from open or closed excision as advocated in 1942 nor have they improved on its success rate [4,[6][7][8]. Fortunately, others are performing more contemporary procedures which provide greater success.…”
Section: Discussionmentioning
confidence: 99%
“…A recent national survey from the Netherlands on the surgical treatment of PD concluded that traditional excision techniques are still the most frequently performed in that country, but the majority of surgeons and surgical residents remain unsatisfied with the current treatments [10].…”
Section: Introductionmentioning
confidence: 99%